Conformational Altered p53 as an Early Marker of Oxidative Stress in Alzheimer's Disease - Buizza, Laura; Cenini, Giovanna; Lanni, Cristina; Ferrari-Toninelli, Giulia; Prandelli, Chiara; Govoni, Stefano; Buoso, Erica; Racchi, Marco; Barcikowska, Maria; Styczynska, Maria; Szybinska, Aleksandra; Butterfield, David Allan; et al. (PLOS ONE, 2012)
In order to study oxidative stress in peripheral cells of Alzheimer's disease (AD) patients, immortalized lymphocytes derived from two peculiar cohorts of patients, referring to early onset AD (EOSAD) and subjects harboured AD related mutation (ADmut), were used. Oxidative stress was evaluated measuring i) the typical oxidative markers, such as HNE Michel adducts, 3 Nitro-Tyrosine residues and protein carbonyl on protein extracts, ii) and the antioxidant capacity, following the enzymatic kinetic of superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione reductase (GRD). We found that the signs of oxidative stress, measured as oxidative marker levels, were evident only in ADmut but not in EOSAD patients. However, oxidative imbalance in EOSAD as well as ADmut lymphocytes was underlined by a reduced SOD activity and GRD activity in both pathological groups in comparison with cells derived from healthy subjects. Furthermore, a redox modulated p53 protein was found conformational altered in both EOSAD and ADmut B lymphocytes in comparison with control cells. This conformational altered p53 isoform, named “unfolded p53”, was recognized by the use of two specific conformational anti-p53 antibodies. Immunoprecipitation experiments, performed with the monoclonal antibodies PAb1620 (that recognizes p53wt) and PAb240 (that is direct towards unfolded p53), and followed by the immunoblotting with anti-4-hydroxynonenal (HNE) and anti- 3-nitrotyrosine (3NT) antibodies, showed a preferential increase of nitrated tyrosine residues in unfolded p53 isoform comparing to p53 wt protein, in both ADmut and EOSAD. In addition, a correlation between unfolded p53 and SOD activity was further found. Thus this study suggests that ROS/RNS contributed to change of p53 tertiary structure and that unfolded p53 can be considered as an early marker of oxidative imbalance in these patients.